Efikasi Diri dan Kepercayaan Diri Mahasiswa PGSD terkait Kecemasan Berbicara di Depan umum - Fatmah, Nor; Anward, Hemy Heryati; Mayangsari , Marina Dwi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2021)
This study aims to find out whether there is a role of self-efficacy and self-esteem towards public speaking anxiety in students of Primary School Teacher Education Department (PGSD), Lambung Mangkurat University. The subjects in this study were 60 students, selected using a quota sampling technique. Data were collected using Likert scale model consisting of self-efficacy scale, self-esteem scale, and public speaking anxiety scale. The data were analyzed using multiple linear regression and the result showed that: (1) there was a role of self-efficacy towards public speaking anxiety as indicated by the value of -t count < -t table (-5.558 < -2.002); (2) there was a role of selfesteem towards public speaking anxiety, as indicated by the value of -t count < -t table (-4.106 < -2.002); (3) there was interaction of self-efficacy and self-esteem with public speaking anxiety, as indicated by F count > F table = (24.428 > 3.159). It can therefore be concluded that the self-efficacy and self-esteem together had a role by 46.2% towards the public speaking anxiety in students of Primary School Teacher Education Department (PGSD), Lambung Mangkurat University, while the remaining 53.8% was contributed by other factors that were not examined in this study.